Свободу Змею Горынычу! - Благов Владимир (Новые сказочные повести, 2011)
Экземпляры: ДБ (201310) / Инвентарный номер: 48609 / Цена: 86.00 / Сис.шифр: Р2мл / Авт.знак: Б 68 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6